0246 Rest-activity Circadian Rhythm And Hair Cortisol Among Toddlers Living In Socioeconomically Disadvantaged Communities. (12th April 2019) - Ordway, Monica R; Jeon, Sangchoon; Sadler, Lois; Canapari, Craig; Redeker, Nancy
Abstract: Introduction: Early childhood adversity renders young children vulnerable to the physical effects of a prolonged stress response and socioemotional effects of being unable to verbalize the subjective feeling of stress. This study examined the associations between objective measures of chronic stress and the timing and regularity of daily activities among toddlers. Understanding these associations can help elucidate rest-activity patterns that place young children at risk for desynchronized circadian patterns that ultimately place them at risk for developing diabetes, obesity, and certain cancers independent of overall exposure. Methods: A sample of 64 healthy toddlers living in socioeconomically low resourced communities wore an actigraph for 9 days and nights. Rest-activity patterns were generated from cosignor analysis (MESOR, amplitude, acrophase) and non-parametric circadian rhythm analysis (IS:interdaily stability; IV: intradaily variability). Chronic stress was measured by hair cortisol. We examined the associations between toddlers' rest-activity patterns and log-transformed hair cortisol levels with Pearson correlation coefficients. Results: The sample included 64 toddlers (Mean age=14.84 months, SD=2.72; 61% female). The children lived predominantly in single (70%), low income (86% income under $40, 000) households. Overall, there was large variability in activity between days indicated by a low: IS=.02. There was a low level of fragmentation of the sleep-wake rhythm (IV=.27). The MESOR mean was 268.83 (SD=83.15) and amplitude mean was 249.53 (SD=87.55) with boys slightly but non-significantly higher. The mean hair cortisol level was 118pg/mg (SD=174.87) with boys non-significantly higher. Overall, hair cortisol was not associated with rest-activity patterns. However, there were significant sex differences; increased activity was associated with increased hair cortisol levels in boys (MESOR: r=.47, p=.02; Amplitude: r=.51, p=.01) and lower hair cortisol in girls (MESOR: r=-.27, p=.09; Amplitude: r=-.35, p=.03) Conclusion: Our findings suggest that rest-activity patterns are similar among boys and girls but their patterns have an opposing relationship with chronic stress. Future studies should consider the unique socioecological influences on boys and girls and incorporate longitudinal analysis. Interventions to improve sleep and buffer toxic stress may require consideration of children's gender. Support (If Any): 1K23NR01627701A NIH/NINR.